A Literature Review: The Effectiveness of Problem-Based Learning (PBL) Based E-Module to Improve Students' Critical Thinking Skills - Elya Suci Nabila; Fitria Herawadini; Diyah Nurmayanti; Fitri Muslihatun (Indonesian Publication Center, 2026)
Critical thinking skills are an essential 21st-century competency that students must master. However, PISA 2022 results show that Indonesian students' achievement remains below the OECD average, indicating low higher-order thinking skills. This study aims to identify trends in the development of Problem-Based Learning (PBL)-based e-modules across various educational levels between 2014 and 2026, assess their practicality and effectiveness, and analyze their impact on critical thinking skills. The method used was a Systematic Literature Review (SLR) analyzing 11 relevant research articles. The study results indicate that PBL-based e-modules are consistently effective in improving students' critical thinking skills. This is demonstrated by N-gain values ??ranging from 0.50 to 0.76 (medium to high category). This effectiveness is supported by the presentation of contextual problems, the use of scaffolding, and the flexibility of independent learning that can activate higher-order cognitive processes. Thus, PBL-based e-modules have the potential to become effective, innovative teaching materials to improve the quality of learning and critical thinking skills of students at various levels and subjects.